2016
DOI: 10.1002/mma.4007
|View full text |Cite
|
Sign up to set email alerts
|

Existence and multiplicity of systems of Kirchhoff‐type equations with general potentials

Abstract: This paper is concerned with the following systems of Kirchhoff‐type equations: −()a+b∫double-struckRN|∇u|2dxnormalΔu+V(x)u=Fu(x,u,v),x∈double-struckRN,−()c+d∫double-struckRN|∇v|2dxnormalΔv+V(x)v=Fv(x,u,v),x∈double-struckRN,u(x)→0,1em1em1em1emv(x)→01em1em1em1em1em1em1em1em1em1em1em1em1em1em1emas1em|x|→∞. Under more relaxed assumptions on V(x) and F(x,u,v), we first prove the existence of at least two nontrivial solutions for the aforementioned system by using Morse theory in combination with local linking ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…See, for example, the literature. () Let us briefly recall some known results on system . In previous study, D'Aprile and Mugnai considered for the case of f ( x , u )=| u | p −2 u and V ( x )=1, i.e., {arrayΔu+u+ϕu=|ufalse|p2u,arrayindouble-struckR3,arrayΔϕ=u2,arrayindouble-struckR3. …”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…See, for example, the literature. () Let us briefly recall some known results on system . In previous study, D'Aprile and Mugnai considered for the case of f ( x , u )=| u | p −2 u and V ( x )=1, i.e., {arrayΔu+u+ϕu=|ufalse|p2u,arrayindouble-struckR3,arrayΔϕ=u2,arrayindouble-struckR3. …”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…In [27,30], Z. Zhang et al studied the existence of nontrivial solutions and sign-changing solutions for (1). The study of systems of Kirchhoff type equations can be found in [6,8,13,14,29,32]. Critical problems involving nonlocal operators creat many difficulties in applying variational methods.…”
Section: Introductionmentioning
confidence: 99%